Entangled Discourses South-North Orders of Visibility - Kerfoot, Caroline; Hyltenstam, Kenneth (Taylor & Francis, 2017)
This book uniquely explores the shifting structures of power and unexpected points of intersection - entanglements - at the nexus of North and South as a lens through which to examine the impact of global and local circuits of people, practices and ideas on linguistic, cultural and knowledge systems. The volume considers the entanglement of North and South on multiple levels in the contemporary and continuing effects of capitalism, colonialism, and imperialism, in the form of silenced or marginalized populations, such as refugees, immigrants, and other minoritised groups, and in the different orders of visibility that make some types of practices and knowledge more legitimate and therefore more visible. It uses a range of methodological and analytical frames to shed light on less visible histories, practices, identities, repertoires, and literacies, and offer new understandings for research and for language, health care, education, and other policies and practices. The book brings together an exciting mix of voices of both established and new scholars in multilingualism and diversity from a range of social, political, and historical contexts and provides coverage of areas previously underrepresented in current research on multilingualism, globalization, and mobility, including Brazil, South Africa, Australia, East Timor, Wallis and Mayotte, Cape Verde and Guinea-Bissau. This volume is key reading for scholars, researchers, and graduate students in multilingualism, globalisation, sociolinguistics, mobility and development studies, applied linguistics, and language and education policy.